Effects of combination antiretroviral therapies on the risk for myocardial infarction among HIV patients - Brouwer, Emily S. (2014)
BACKGROUND: Cohort studies have demonstrated greater risk of myocardial infarction (MI) associated with specific antiretroviral use, while meta-analyses of randomized controlled trials have not. These differences may be due to inherent biases in the observational study design or to the limited duration of randomized trials. We conducted a new-user, active-comparator cohort study emulating a randomized controlled trial comparing initiation of several antiretrovirals as part of combination antiretroviral therapy (cART) and MI. METHODS: We included North Carolina (NC) Medicaid beneficiaries infected with HIV between 2002 and 2008 who were previously untreated with cART. We compared hazard ratios (HRs) and 95% confidence intervals (CIs) of MI between abacavir and tenofovir recipients, and lopinavir-ritonavir or atazanavir recipients and non-nucleoside-reverse-transcriptase-inhibitor (NNRTI) recipients. We adjusted for confounding through inverse-probability-weighting methods. RESULTS: There were 3,481 NC Medicaid new cART recipients who contributed 6,399 person-years and experienced 38 MI events. Receiving abacavir compared with tenofovir as part of cART was associated with an increased rate of MI unadjusted (HR= 2.70 [95% CI= 1.24 - 5.91]; HR= 2.05 [0.72 - 5.86]). Point estimates also suggest a relationship between receipt of atazanavir or lopinavir-ritonavir compared with an NNRTI and MI, although, estimates were imprecise. CONCLUSIONS: We found an increased rate of MI among patients initiating abacavir compared with tenofovir although the association was decreased after confounding adjustment. Without a very large prospective comparative clinical trial, a much larger observational study of patients initiating cART would be needed to better define this apparent association.